2015
DOI: 10.5194/acp-15-4179-2015
|View full text |Cite
|
Sign up to set email alerts
|

Absorption of aerosols above clouds from POLDER/PARASOL measurements and estimation of their direct radiative effect

Abstract: Abstract. This study presents an original method to evaluate key parameters for the estimation of the direct radiative effect (DRE) of aerosol above clouds: the absorption of the the cloud albedo. It is based on multi-angle total and polarized radiances both provided by the A-train satellite instrument POLDER -Polarization and Directionality of Earth Reflectances. The sensitivities brought by each kind of measurements are used in a complementary way. Polarization mostly translates scattering processes and is t… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
132
0

Year Published

2015
2015
2020
2020

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 72 publications
(136 citation statements)
references
References 63 publications
4
132
0
Order By: Relevance
“…In addition, CALIOP underestimates aerosols at altitudes above 4 km (Watson‐Parris et al, ). Although the regional cloudy‐sky radiative effects of ari can be strongly positive (de Graaf et al, ; Keil & Haywood, ; Peers et al, ), a small globally averaged cloudy‐sky RFari is expected because most of anthropogenic aerosols are located in the planetary boundary layer, where their RFari is masked by dense water clouds or partially masked by ice clouds. Indeed, GCMs tend to put too much aerosol mass aloft compared to CALIOP vertical aerosol extinction profiles (Koffi et al, ), so even the small cloudy‐sky RFari reported by Schulz et al () may be an overestimate.…”
Section: Rf Of Aerosol‐radiation Interactionsmentioning
confidence: 99%
“…In addition, CALIOP underestimates aerosols at altitudes above 4 km (Watson‐Parris et al, ). Although the regional cloudy‐sky radiative effects of ari can be strongly positive (de Graaf et al, ; Keil & Haywood, ; Peers et al, ), a small globally averaged cloudy‐sky RFari is expected because most of anthropogenic aerosols are located in the planetary boundary layer, where their RFari is masked by dense water clouds or partially masked by ice clouds. Indeed, GCMs tend to put too much aerosol mass aloft compared to CALIOP vertical aerosol extinction profiles (Koffi et al, ), so even the small cloudy‐sky RFari reported by Schulz et al () may be an overestimate.…”
Section: Rf Of Aerosol‐radiation Interactionsmentioning
confidence: 99%
“…Nair et al, 2013). Absorbing aerosols above clouds (AACs) also create a positive DRE at TOA since aerosols absorb cloud reflection Chand et al, 2009;Peters et al, 2011;Jethva et al, 2013;Meyer et al, 2013Meyer et al, , 2015Zhang et al, 2014Zhang et al, , 2016Feng and Christopher, 2015;Peers et al, 2015). Additionally, the presence of AACs can lead to an underestimation of cloud optical thickness (COT) retrieval at visible wavelengths compared to the retrieval of COT in a pristine cloudy scene (Haywood et al, 2004;Coddington et al, 2010;Meyer et al, 2013).…”
Section: Introductionmentioning
confidence: 99%
“…Above highly reflective clouds, their Direct Radiative Effect (DRE) is usually positive because aerosol absorption reduces local planetary albedo. Recent studies based on remote sensing observations have shown that the DRE of Above‐Cloud Aerosols (ACA) is typically strong over the SEAO and can reach instantaneous values larger than +130 Wm −2 [ DeGraaf et al , ; Peers et al , ]. However, global aerosol models do not reproduce such high DRE [ DeGraaf et al , ].…”
Section: Introductionmentioning
confidence: 99%